2019
DOI: 10.1007/s42454-019-00003-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between physiological signals and stress levels in the case of automated technology failure

Abstract: Although successful automation can bring abundance to people's lives, the prolonged use of unreliable automation causes negative impacts on users. This study aims to examine how prolonged use of an unreliable auto-proofreading system affects users' trust levels and physiological responses. Nineteen native English speakers participated in tasks that correct grammatical errors in each of the 20 sentences in reliable and unreliable proofreading conditions. During the tasks, the participants' electrodermal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The general assumption of this study is that an AI failure and unreliability cause increased stress based on a low trust in AI system operations owing to unpredictable AI reactions. A connection between trust and stress was described in previous research [9], [33], where it was found that AI mistakes and unreliability cause a higher cognitive workload and mental stress with decreased user trust. In other words, if the AI system fails or is unreliable, then the operator stress increases and the trust level decreases.…”
Section: B Relationships Among Emotional State Perception and Ai Operation Of Usersmentioning
confidence: 74%
See 2 more Smart Citations
“…The general assumption of this study is that an AI failure and unreliability cause increased stress based on a low trust in AI system operations owing to unpredictable AI reactions. A connection between trust and stress was described in previous research [9], [33], where it was found that AI mistakes and unreliability cause a higher cognitive workload and mental stress with decreased user trust. In other words, if the AI system fails or is unreliable, then the operator stress increases and the trust level decreases.…”
Section: B Relationships Among Emotional State Perception and Ai Operation Of Usersmentioning
confidence: 74%
“…2) APPARATUS A previous program developed using Visual Studio C# (Visual Studio 2015, Microsoft Co., USA) was applied to conduct the experiment [33], [34]. The program included four different auto-proofreading sessions (i.e., sessions A, B, C, and D) [9]: Session A: A reliable auto-proofreading condition indicating a grammatical error with an underline and without providing a suggestion (word).…”
Section: B Experiments 2: English Proofreading Software Using Ai 1) Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The airbag control unit (ACU) can be improved with adaptive strategies depending on the actual occupant positions once the crash is going to occur (Depottey and Schneider 2007;Farmer and Jain 2003;Hall et al 2008, Schneider andRose 2010). So, future intelligent vehicles should be capable of monitoring also the inside scenario with physical and physiological measures (Branstrom et al 2019;Teo et al 2019).…”
Section: Introductionmentioning
confidence: 99%